Specifics of Asset Impairment in the Conditions of Armed Aggression - Andrii Kulyk (Облік і фінанси, 2022)
A decrease in the value of the assets of enterprises due to direct damage or destruction, as well as a decrease in expected benefits due to the deterioration of the external environment in which the business operates, are the consequences of the Russian Federation's armed aggression in Ukraine. Therefore, the issue of accounting approaches and procedures for assessing losses from asset impairment becomes relevant. The article aims to define and critically analyze the features of the procedures for the impairment of fixed assets in connection with armed aggression. Signs of impairment are identified, the analysis of which is a prerequisite for assessing losses from the impairment of fixed assets. Cases and problematic aspects of implementing asset impairment procedures in conditions of armed aggression have been identified. Among them are the instability of the external environment, the need to update business plans, the development of several cash flow forecast scenarios, and the need to take into account additional risks from armed aggression in the discount rate. Methods of fair value assessment proposed in international valuation standards were disclosed. When identifying assets subject to an impairment test, it is proposed to create a register of objects that have suffered from armed aggression. When choosing between the assessment of fair value and value-in-use, the author concluded that determining fair value is a more difficult task, as it is based to a greater extent on external market assumptions. In contrast, the calculation of value-in-use is a more feasible task for the company's management, provided that the business is updated on time – plans and forecasts.